Unknown Like Ḹ: Complications in Sanskrit "Alphabet Poem" Stotras - Buchta, David (JAOS, 2024)
Beginning with Rūpa Gosvāmin (late fifteenth century-1564), at least four poets composed poems in the Sanskrit virudāvalī genre that included akṣamayī kalikās, rhythmic compositions wherein each successive segment begins with the letters of the Sanskrit varṇakrama, from a to kṣa, in sequence. The fact that a number of the letters of the varṇakrama rarely or never occur in word-initial position, including the nasals ṅa, ña, and ṇa, the retroflex consonants, the aspirated consonants jha and tha, the anusvāra and visarga, and the vowels ṝ, ḷ, and especially ḹ, creates potential obstacles in the composition of such poems. This paper examines the four known works with these "alphabet poems," and identifies six strategies that the poets employed in coining epithets beginning with such challenging letters: 1) the use of ekākṣarakoṣas, dictionaries of single-letter words, 2) reference to the shapes of the written letter, 3) onomatopoeia, 4) grammatical derivations, 5) fictitious sandhi-based back-derivations, and 6) metalinguistic puns. The paper thus argues that the difficulty these letters present was, for these poets, a desirable feature of this structure, allowing them to display their learning, whether in service of a royal patron or in a context of Vaiṣṇava devotion.